Pendampingan musyawarah lailiyah Pondok Pesantren Raudlatul Ulum 1 Putra - Arisih, Wesil; Hilam, Husnul; Husni, Muhammad (Nur Science Institute, 2025)
This community service program aims to assist the Musyawarah Lailiyah (Nightly Discussion Forum) at Raudlatul Ulum 1 Putra Islamic Boarding School as an effort to cultivate students with strong capacities in Islamic jurisprudence (fiqh) and classical Islamic texts. Musyawarah Lailiyah serves as a structured forum that focuses on enhancing students' abilities to interpret classical texts (ta'bir) and analyze fiqh issues in depth. The mentoring method applied includes participatory approaches, facilitator training, flexible scheduling, and regular evaluation. The results of this program show a significant improvement in the quality of discussions, active student participation, and students' ability to formulate fiqh-based reasoning using traditional references. Additionally, improvements in program management and in the use of supporting resources, such as classical books and digital media, were observed. This program fosters a more dynamic academic atmosphere in the pesantren and helps shape students into critical, analytical thinkers ready to become future religious leaders.